2012
DOI: 10.1007/s13277-012-0614-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PKCα activation in TF/VIIa/PAR2-induced proliferation, migration, and survival of colon cancer cell SW620

Abstract: Our previous study has demonstrated that protease-activated receptor 2 (PAR2) activation mediated by tissue factor (TF)/VIIa complex triggers the ERK1/2/NF-κB signaling pathway, which further contributes to the proliferation and migration of colon cancer cell line SW620. However, the detailed mechanisms remain unclear. This study was to investigate whether protein kinase Cα (PKCα) is involved in these events and the possible mechanism. The results revealed that PAR2-activating peptide or VIIa could induce time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 45 publications
0
46
0
2
Order By: Relevance
“…It has been reported that PKCα could inhibit the occurrence of intestinal cancer and the expression level of PKCα in colorectal cancer cells is low relative to other cancers [33,34]. In contrast, some studies have shown that PKCα activation can promote cancer cell proliferation, migration, survival, and drug resistance [35][36][37]. In colorectal cancer, the PKCα inhibitor can reduce cell viability and inhibit cell migration [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PKCα could inhibit the occurrence of intestinal cancer and the expression level of PKCα in colorectal cancer cells is low relative to other cancers [33,34]. In contrast, some studies have shown that PKCα activation can promote cancer cell proliferation, migration, survival, and drug resistance [35][36][37]. In colorectal cancer, the PKCα inhibitor can reduce cell viability and inhibit cell migration [38].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of cell growth in colon cancer cells by PKC is thought to occur through the regulation of EGFR signaling [110]; ERKmediated inhibition of the inhibitor of DNA binding 1, a proproliferative factor [112]; downregulation of -catenin and its target genes cyclin D1 and c-Myc [111,113]; and PKCmediated phosphorylation of retinoic acid-related orphan nuclear receptor , which downregulates the Wnt/ -catenin signaling [114]. In contrast to these results, a recent study has suggested that PKC activation is involved in the activation of ERK1/2/NF-B through the tissue factor/VIIa/PAR2 pathway and this signaling pathway leads to enhanced proliferation, migration, and survival for the colon cancer cell line SW620 [115].…”
Section: Colonmentioning
confidence: 99%
“…149 Other PAR2 activators like kallikrein 14 (KLK14) induced cell signaling in colon cancer cells by activating PAR2, leading to proliferative responses. 150 There are also reports suggesting that TF/FVIIa induced PAR2 activation, leading to proliferation and migration of SW620 colon cancer cells, 151,152 as well as inducing signaling, migration, and invasion of breast cancer cells. 86,153 In addition, PAR2-induced β-arrestin signaling has been shown to mediate migration of breast cancer cells, 154,155 although it is likely that other pathways are important in migration.…”
Section: ■ Par2 Functional Phenotypementioning
confidence: 99%
“…Other non-polar and polar/charged groups, including serine mimetics and nonaromatic heterocycles, in derivatives of GB88 (147)(148)(149)(150)(151)(152) were either inactive or displayed less antagonist activity than GB88. This suggested that aromaticity may be important for potency.…”
Section: Gb88mentioning
confidence: 99%
See 1 more Smart Citation